Bibliometric Analysis of Ecological Literature - Biradar, B. S.; Mathad, Sujatha (Journal of Information and Knowledge, 2000)
Study is based on the references appended to the articles appeared in the journal of Annual Review of Ecology and Systematics for the year 1995-1996. Identifies the major forms of literature, core journals, authorship pattern, obsolescence of literature etc. Study shows that maximum number of citations are from USA (63.966%), Single author papers claim 34.694% and more than 80% of the citations fall in the age group of 0-15 years.